Distribución de los Rudistas (Bivalvia) del Cretácico superior sudpirenaico. - Pons, J.M. (Cuadernos de Geología Ibérica, 1982)
The stratigraphical and geographical distribution of 44 species of Hippuritidae and 71 species of Radiolitidae, recorded from the Upper Cretaceous of Catalan Prepyrenees, is presented.